IBN AL-AL-'ARABI'S CONCEPTION OF RELIGION - Mohd Sani Badron (Penerbit IKIM, 2012)
This work begins with the discourses of the Quran and Prophetic tradition on Islam and other religious traditions. It then presents a historical survey of Muslim works in the field of comparative study of religions written by philosophers, theologians, and sufis. The work also deals with the background of Ibn al-'Arabi, arguably the greatest representative of the sufis. Subsequent chapters discuss his general conception of religion, and his interpretation of Quranic terminologies such as islam, din, fitrah, mithaq, iman, kufr, shariah, minhaj, nubuwwah, risalah, millah and ummah.